The Making of Entrepreneurs in Germany : Are Native Men and Immigrants Alike? - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2004)
This paper uses a state of the art three-stage technique to identify the characteristics of the self-employed immigrant and native men in Germany and to understand their underlying drive into self-employment. Employing data from the German Socioeconomic Panel 2000 release we find that self-employment is not significantly affected by exposure to Germany or by human capital. But this choice has a very strong intergenerational link and it is also related to homeownership and financial worries. While individuals are strongly pulled into selfemployment if it offers higher earnings, immigrants are additionally pushed into selfemployment when they feel discriminated. Married immigrants are more likely to go into selfemployment, but less likely when they have young children. Immigrants living with foreign passports in ethnic households are more likely self-employed than native Germans. The earnings of self-employed men increase with exposure to Germany, hours worked and occupational prestige; they decrease with high regional unemployment to vacancies ratios. Everything else equal, the earnings of self-employed Germans are not much different from the earnings of the self-employed immigrants, including those who have become German citizens. However, immigrants suffer a strong earnings penalty if they feel discriminated against while they receive a premium if they are German educated.
Keywords: J24; J31; M13; J61; J23; 330; entrepreneurship; self-employment; occupational choice; immigrants; wage differentials; Selbstständige; Unternehmer; Migranten; Berufswahl; Lohndifferenzierung; Schätzung; Deutschland